Effect of chronic comorbidities on quality of life of gynecologic cancer patients in Puerto Rico - Gloriáliz G. Santiago-Pérez; Claudia P. Amaya-Ardila; Sharee A. Umpierre; Ana P. Ortiz-Martinez (Pan American Health Organization, 2022)
Objective. To describe prevalence of chronic diseases and evaluate associations between comorbidities and quality of life in gynecologic cancer patients in Puerto Rico. Methods. A cross-sectional study among 233 women aged ≥21 years with a gynecologic cancer diagnosis. Through telephone interviews, information on comorbidities, quality of life, and other covariates were assessed. Quality of life included six items, assessing physical and mental health. Multivariate logistic regression models were used to estimate magnitude of association between the comorbidities under study (diabetes, cardiovascular and autoimmune diseases) and quality-of-life items, through adjusted prevalence odds ratio (aPOR; 95% confidence interval [CI]). Results. Most women (90.1%) reported one or more comorbidities in addition to their cancer diagnosis; cardiovascular diseases (63.1%) were more common than autoimmune diseases (37.3%) and diabetes (33.9%). Between 30% and 40% of the sample indicated dysfunctions in their general health (39.5%) and frequent physical (33.9%) and mental distress (31.8%). Adjusting for age and gross family income, women with autoimmune diseases presented higher prevalence of frequent limitations for daily activities (aPOR 2.00; 95% CI 1.05-3.81), poor general health (aPOR 3.52; 95% CI 1.90-6.49), frequent mental distress (aPOR 2.19; 95% CI 1.19-4.03), and dissatisfaction with life (aPOR 4.86; 95% CI 1.82-12.95) compared to those who did not report autoimmune diseases. No associations with cardiovascular diseases and diabetes were observed. Conclusions. Quality-of-life dysfunctions were highly prevalent in this population of gynecologic cancer patients. Suffering from autoimmune comorbidities significantly exacerbated those dysfunctions.